Peningkatan Keterampilan Proses Sains Pada Proses Metode Eksperimen - Yunesti, Dilla (LENTERNAL: Learning and Teaching Journal, 2022)
The objective of the research was to explain the process an learning outcomes of thought the application of experiment method to increase science process skills of group B1 Kingdergarden Fhatimah Bukareh in 2021/2022. The subject of research are 16 children. The method used in this research is an action research which refers to the odel of a Classroom Action Research Kemmis dan Mc. Taggart consist of four phase: planning, actions. observation and reflection. This research cinsist of two cycles, each eycle cosist of 8 times in actions. The data analysis technique used in this research are a quqlitative an quantitative analysis. Analysis of data reduction, data display and data verification. Analysis of quantitative data descriptive statistics that explain intable and grafic. The result of research n that increase science process skills of children through the application of experiment method, it can beproven scoring average pre-intervention is 45,31%, the first cycle is 65,44%, and the second cycleis 89,05%.